VISIONARY LEADERSHIP AND THE SELF EFFICACY WITH ORGANIZATIONAL COMMITMENT - Suryadi SYARIF; Lina HERLINA (Journal of Education and Leadership in Education, 2019)
The aims of this study is to identify and analyze the relationship between school principal visionary leadership and teacher’s self-efficacy toward teacher’s organizational commitment. The study used a survey method. Population of 223 teachers, and a sample of 143 teachers. Data collected by questionnaire technique. Data analyzed with correlation and regression techniques. The results showed that: 1) there is a positive and significant relationship between the visionary leadership of the head teacher of the school with organizational commitment; 2) there is a positive and significant relationship between self-efficacy with organizational commitment of teachers; and 3) there is a positive and significant relationship between the visionary leadership of the principal and teacher self-efficacy simultaneously with organizational commitment of teachers. Its impliaction, the teacher organizational commitment can be enhanced through the visionary leadership of the principal and teacher self-efficacy.